Reward- and aversion-related processing in the brain: translational evidence for separate and shared circuits - Dave J. Hayes (Frontiers Research Topics, 2016)
Affective brain circuits underpin our moods and emotions. Appetitive and aversive stimuli from our exteroceptive and interoceptive worlds play a key role in the activity of these circuits, but we still do not know precisely how to characterize these so-called reward-related and aversion-related systems. Moreover, we do we yet understand how they interact anatomically or functionally. The aim of the current project was to gather some translational evidence to help clarify the role of such circuits. A multi-dimensional problem in its own right, the book contains 14 works from authors exploring these questions at many levels, from the cellular to the cognitive-behavioral, and from both experimental and conceptual viewpoints. The editorial which introduces the book provides brief summaries of each perspective (Hayes, Northoff, Greenshaw, 2015). While questions of how to accurately define affect- and emotion-related concepts at the psychological level are far from answered, here we have attempted to provide some insight into the brain-based underpinnings of such processes. The near future will undoubtedly involve making new inroads and will require the joint efforts of behavioral, brain-based, and philosophical perspectives to do so.